Oxytocin versus carbetocine to prevent post partum hemorrhage following cesarean section - Navarro Díaz, Begoña (2014)
Background: Postpartum haemorrhage (PPH) is the single most important cause of maternal mortality, and uterine atony is its most common cause. The best treatment is prevention. Oxytocin reduces the risk of PPH. In Spain carbetocin has been marketed, a human oxytocin analogue that has rapid onset of action and an average life 4-10 times longer than oxytocin, producing tonic contraction that reduces postpartum blood loss. Objectives: To compare effects of carbetocin and oxytocin, in order to prevent postpartum haemorrhage after cesarean section. Design: Observational retrospective comparative study. Setting: Obstetrics and Gynecology Service, Hospital General Universitario de Elche, Alicante, España. Participants: Pregnant women with risk factor of uterine atony following cesarean section. Methods: From April 2010 through March 2012 247 women with a risk factor for uterine atony after cesarean section The effects of administering 100 micrograms of carbetocin and 10 UI of oxytocin following delivery were compared. Hemoglobin levels prior and 24-48 hours after cesarean section and the percentage of transfusions given were assessed. Main outcome measures: Anemia, blood transfusions, intravenous iron. Results: In the group of carbetocin, hemoglobin decreased less than in the oxytocin group (P=0.56), and there was less anaemia after cesarean section (P=0,852). Transfusions and intravenous iron did not provide conclusive data. Conclusions: There were no significant differences between carbetocin and oxytocin to prevent PPH after cesarean sections.